INFLUENCE OF SELF-EFFICACY, LEARNING INTEREST, AND FAMILY ENVIRONMENT ON SCIENCE LEARNING OUTCOMES - Suprapto; Sudarmiani; Nurhadji Nugraha (International Journal of Teaching and Learning, 2024)
This research aims to determine the influence of self-efficacy, learning interest, and family environment on learning outcomes. This research method is descriptive qualitative. The subjects were class X students. Data collection techniques used questionnaires and documentation. Data analysis techniques used are classical assumption testing, multiple regression analysis, and hypothesis testing. The research results show: 1) there is a significant influence between self-efficacy and learning outcomes, indicated by a coefficient value of 0.226, which means that every 0.226 increase in self-efficacy is accompanied by an increase in learning outcomes. 2) There is a significant influence between learning interest and learning outcomes, which indicated by a coefficient value of 0.221, means that every 0.221 increase in learning interest is accompanied by an increase in learning outcomes. 3) There is a significant influence between the family environment and learning outcomes, indicated by a coefficient value of 0.304, which means that every increase of 0.304 in the family environment is accompanied by an increase in learning outcomes. 4) Self-efficacy, learning interest, and the family environment simultaneously have a significant influence on the science learning outcomes. This shows that the higher the self-efficacy, interest in learning, and family environment, the higher the learning outcomes.